A Nonfluoroscopic Technique for Coronary Arteries Three‐Dimensional Mapping during Epicardial Ventricular Tachycardia Ablation. Issue 3 (17th January 2017) - CALZOLARI, VITTORIO; BARBATO, GAETANO; CROSATO, MARTINO; DE MATTIA, LUCA; DANIOTTI, ALESSANDRO; INDIANI, STEFANO; SQUASI, PAOLO ANTONIO MARIA; OLIVARI, ZORAN
Abstract : When performing epicardial ablation of ventricular tachycardia (VT), caution must be taken not to damage the coronary arteries. We report a case in which a new, nonfluoroscopic technique for incorporating an accurate, real‐time reconstruction of the main coronary vessels into a three‐dimensional electroanatomic map was used for epicardial VT ablation.